Forgottenness : a novel - Mali͡archuk, Tani͡a, 1983- (Liveright Publishing Corporation, 2024)
An award-winning novel from one of Ukraine's most prolific contemporary authors, Forgottenness tells a spellbinding story of belonging and uprootedness, as understood by two exiles across time. An exceedingly anxious narrator grapples with a host of conditions, from obsessive-compulsive disorder to a creeping sense of agoraphobia. As her symptoms deepen, she finds unexpected solace researching Viacheslav Lypynskyi a social and political activist of Polish descent who played a pivotal role in the struggle for Ukrainian independence and who nursed his own comorbidities. In this long-deceased ideologue the narrator finally finds companionship, mining her country's history in pursuit of a better grasp over her own. Brilliantly translated by Zenia Tompkins, Forgottenness movingly illuminates the intricacies of the Ukrainian experience and announces Tanja Maljartschuk as an essential voice in contemporary world literature.--Publisher description.